Developing sociopolitical consciousness of race and social class inequality in adolescents attending progressive and no excuses urban secondary schools. Issue 3 (3rd July 2018) - Seider, Scott; Graves, Daren; El-Amin, Aaliyah; Soutter, Madora; Tamerat, Jalene; Jennett, Pauline; Clark, Shelby; Malhotra, Saira; Johannsen, Jamie
ABSTRACT: Sociopolitical consciousness refers to an individual's ability to critically analyze the political, economic, and social forces shaping society and one's status in it. A growing body of scholarship reports that high levels of sociopolitical consciousness are predictive in marginalized adolescents of a number of key outcomes including resilience and civic engagement. The present study explored the role that urban secondary schools can play in fostering adolescents' sociopolitical consciousness through a longitudinal, mixed methods investigation of more than 400 adolescents attending "progressive" and "no excuses" charter high schools. Analyses revealed that, on average, students attending progressive high schools demonstrated sizeable shifts in their sociopolitical consciousness of racial inequality, and students attending no excuses high schools demonstrated sizeable shifts in their sociopolitical consciousness of social class inequality. Qualitative interviews with participating students offered insight into the curriculum, programming, and practices that these youth perceived as contributing to these differences in their sociopolitical consciousness.